PP05 The First Choice Of Health Institutions Of Elderly In Zhejiang And Qinghai, China. (2019) - Zhang, Hao; Wei, Jingming; Gao, Qilong; Zhao, Can; Dong, Hengjin; Hu, Xiaoqian
Abstract : Introduction: The utilization of medical resources in China is unbalanced and insufficient. In order to find a way to maximize their utilization to face challenges in the upcoming decade, this study aims to investigate the elderly's first choice of health institutions when they were ill in the Zhejiang and Qinghai provinces, and to explore the potential pathways related to their choices, respectively. Methods: The data used in this study was from cross-sectional surveys in Zhejiang and Qinghai. According to the Anderson Health Service Utilization Model, we applied structural equation modeling to explore the complex pathways from socioeconomic status (SES), accessibility, and health status to the elderly's first choice of health institutions. Results: The proportion of the elderly who selected community health institutions (CHI) as their first choice of medical institutions in Qinghai was higher than in Zhejiang. The Zhejiang model revealed a significantly negative direct effect of SES and significantly positive direct effects of accessibility to CHI and health status on the choice of institutions, and a significantly positive indirect effect of SES on choice of institutions, through the mediating factor of health status. SES played an important role in the Zhejiang model in direct and indirect ways. In the Qinghai model, only SES and accessibility to CHI had significantly direct effects on the choice of institutions, with accessibility to CHI having the biggest effects. SES had a significant and positive indirect impact on choice of institutions, through the factor of accessibility to CHI. Conclusions: A better understanding of the complex pathways from factors to elderly's choices of health institutions was essential, which may inform priorities for maximizing the utilization of CHI further and prepare to face challenges in the new decade. Through this research method, policymakers could explore the specific pathways based on their own economic and societal status.